Mourning Happiness : Narrative and the Politics of Modernity - Soni, Vivasvan, 1968- (Book collections on Project MUSE., 2010)
For many eighteenth-century thinkers, happiness was a revolutionary idea filled with the promise of the Enlightenment. Vivasvan Soni argues, however, that the period fails to establish the importance of happiness as a guiding idea for human practice, generating our modern sentimental idea of happiness. Mourning Happiness shows how the eighteenth century's very obsession with happiness culminates in the political obsolescence of the idea. Soni explains that this puzzling phenomenon can only be comprehended by studying a structural transformation of the idea of happiness at the level of narrative form. Happiness is stripped of its ethical and political content, Soni demonstrates, when its intimate relation to narrative is destroyed. This occurs, paradoxically, in some of the most characteristic narratives of the period: such eighteenth-century novels as Pamela, The Vicar of Wakefield, and Julie; the pervasive sentimentalism of the time; Kant's ethics; and the political thought of Rousseau and Jefferson. For Soni, the classical Greek idea of happiness--epitomized by Solon's proverb "Call no man happy until he is dead"--Opens the way to imagining a properly secular conception of happiness, one that respects human finitude and mortality. By analyzing the story of Solon's encounter with Croesus, Attic funeral orations, Greek tragedy, and Aristotle's ethics, Soni explains what it means to think, rather than feel, a happiness available for public judgment, rooted in narrative, unimaginable without relationship to community, and irreducible to an emotional state. Such an ideal, Soni concludes, would allow for a radical reenvisioning of a politics that takes happiness seriously and responds to our highest aspirations rather than merely keeping our basest motivations in check.